Liquid Chromatography Tandem Mass Spectrometry Method for Determination of Febuxostat in Human Plasma to Support A Bioequivalence Study - S. Patel, Dinesh; Sharma, Naveen; C. Patel, Mukesh; N. Patel, Bhavin; S. Shrivastav, Pranav; Sanyal, Mallika (Journal of Advanced Pharmaceutical Science And Technology, 2013)
A reliable, selective and sensitive liquid chromatography-tandem mass spectrometry (LC-ESI-MS/MS) assay has been proposed for the determination of febuxostat in human plasma using indomethacin as the internal standard (IS). The analyte and IS were extracted from 200 µL of human plasma via liquid-liquid extraction using methyl tert-butyl ether. Chromatography was performed on Hypurity C18 (100 mm × 4.6 mm, 5 µm) column under isocratic conditions. Detection of analyte and IS was done by tandem mass spectrometry, operating in negative ionization and multiple reaction monitoring mode. The deprotonated precursor to product ion transitions monitored for febuxostat and indomethacin were m/z 315.1 →271.0 and 356.1→312.0 respectively. The limit of detection (LOD) and limit of quantitation (LOQ) of the method were 0.0025 µg/mL and 0.05 µg/mL respectively. The linear dynamic range validated for febuxostat was 0.05-6.00 µg/mL. The intra-batch and inter-batch precision (% CV) was ≤ 7.1 % while the mean extraction recovery was > 87 % for febuxostat across quality control levels. The method was successfully applied to a bioequivalence study of 80 mg febuxostat tablet formulation in 14 healthy Indian male subjects under fasting and fed condition. The reproducibility in the measurement of study data was demonstrated by reanalysis of 110 incurred samples.
Keywords: Febuxostat; LC-MS/MS; liquid-liquid extraction; human plasma; bioequivalence study; incurred sample reanalysis